Structure and Interactions of a Dimeric Variant of sHIP, a Novel Virulence Determinant of Streptococcus pyogenes - Diehl, Carl; Wisniewska, Magdalena; Frick, Inga-Maria; Streicher, Werner; Björck, Lars; Malmström, Johan; Wikström, Mats (Frontiers in Microbiology, 2016)
Streptococcus pyogenes is one of the most significant bacterial pathogens in the human population mostly causing superficial and uncomplicated infections (pharyngitis and impetigo) but also invasive and life-threatening disease. We have previously identified a virulence determinant, protein sHIP, which is secreted at higher levels by an invasive compared to a non-invasive strain of S. pyogenes. The present work presents a further characterization of the structural and functional properties of this bacterial protein. Biophysical and structural studies have shown that protein sHIP forms stable tetramers both in the crystal and in solution. The tetramers are composed of four helix-loop-helix motifs with the loop regions connecting the helices displaying a high degree of flexibility. Owing to interactions at the tetramer interface, the observed tetramer can be described as a dimer of dimers. We identified three residues at the tetramer interface (Leu84, Leu88, Tyr95), which due to largely non-polar side-chains, could be important determinants for protein oligomerization. Based on these observations, we produced a sHIP variant in which these residues were mutated to alanines. Biophysical experiments clearly indicated that the sHIP mutant appear only as dimers in solution confirming the importance of the interfacial residues for protein oligomerisation. Furthermore, we could show that the sHIP mutant interacts with intact histidine-rich glycoprotein (HRG) and the histidine-rich repeats in HRG, and inhibits their antibacterial activity to the same or even higher extent as compared to the wild type protein sHIP. We determined the crystal structure of the sHIP mutant, which, as a result of the high quality of the data, allowed us to improve the existing structural model of the protein. Finally, by employing NMR spectroscopy in solution, we generated a model for the complex between the sHIP mutant and an HRG-derived heparin-binding peptide, providing further molecular details into the interactions involving protein sHIP.